The ambiguity of working class interests in Brazilian road transport: the case of self-employed truckers - Nowak, Jörg (Frontiers in Sociology, 2025)
In many theories on working class power, the formation and existence of the interests of workers is assumed as a given, although it requires political processes for these interests to emerge at all. While this process often remains hidden behind assumptions that trade unions simply represent given economic concerns of workers, the ambiguity and fragility of the formation of working class interests is visible in situations in which the status of the wage earner and/or the self-employed worker is not clear cut or ambiguous, and these situations tend to appear more often in countries of the Global South. Occupations in transport like taxi drivers and truckers are traditionally prone to exhibit these ambiguous situations. This article explores one of those situations with the example of the fragility of the formation of working class interests among Brazilian truckers. The majority of this occupational group consists of self-employed truckers, and in spite of their shared interests with the smaller group of formally employed truckers, they tend to mobilize and organize together with employers, i.e., transport companies. I will explain why this is the case with reference to historical examples and the specific concerns of self-employed truckers and transport companies.